Direct torque control of AC motors using FPGA programming part I - Kiang, Li Rong (2014)
The aim of this project is to utilize Field Programmable Gate Array in Direct Torque control of an Interior Permanent Magnet motor and evaluating the results as compared to what is achieved using Digital Signal Processing from present research studies. Field Programmable Gate Array has been selected for its capability and potential to perform the Direct Torque Control up to a switching frequency of 40 kHz. Using electrical current, Field Programmable Gate Array is able to control the speed at which the shaft of a motor is rotating through voltage vectors by a Three-phase Inverter. The Field Programmable Gate Array (FPGA) has been put through a series of experiments namely the Open loop test and Reverse Torque Control. Results were found to be satisfactory for the Open loop test but not in Reverse Torque Control. However, Field Programmable Gate Array and its program has their limitations in Direct Torque Control. These limitations have significant implications for the commercial application of using Field Programmable Gate Array for Direct Torque Control. Instead, a similar hardware is set up to test the Digital Signal Processing in performing Direct Torque Control and was successful. Lastly, this report will conclude by providing recommendations for future work.